Characteristics of an elliptical ring antenna excited by a linear electric probe - Chawanonphithak, K.; Phongcharoenpanich, C.; Kosulvit, S.; Krairiksh, M. (My University, 2007)
This paper presents the characteristics of an elliptical ring antenna excited by a linear electric probe. Based on the waveguide principle, the suitable cross-sectional dimension of the ring that yields the dominant mode (TEC11 mode) will be formulated in terms of the cut off wavelength. The variation of the antenna characteristics, depending on cross-sectional dimension, ring length and probe length, were investigated using numerical electromagnetic code (NEC) based on the method of moments (MoM). From the experiment, the prototype antenna provides bidirectional pattern with HPBW in E-plane and H-plane of 83 and 46 degrees, respectively, and the gain of 5.1 dBi with SWR 2:1 over the bandwidth of 14% for the operating frequency of 1.92 GHz. This antenna is applicable for mobile communication on a highway, on a street, in a corridor and in a tunnel with the advantages of simple configuration and low cost.
Keywords: Bidirectional antenna; Elliptic cylindrical waveguide; Method of Moments (MoM); Numerical Electromagnetic Code (NEC)